Grit and School Engagement among Adolescents: The Amplifying Role of Teacher Support in Islamic Boarding Schools - Muallifah Muallifah; Beti Malia Rahma Hidayati; Ilhamuddin Ilhamuddin; Sefa Bulut (Universitas Islam Tribakti Lirboyo Kediri, 2024)
School engagement plays a vital role in supporting students’ academic achievement. This study investigates the contribution of grit to school engagement and examines the moderating role of teacher support in this relationship. Unlike previous studies that often explore internal and external factors in isolation, this study adopts a moderation model to analyze the interaction between grit and teacher support simultaneously. A total of 237 junior high school students (94 males, 143 females) from Islamic boarding schools in Malang, Indonesia, were selected through purposive sampling. Data were collected using standardized scales and analyzed using moderated regression analysis in JASP 18.3. The results indicate that grit significantly predicts school engagement (β = 0.433, p = .001). Moreover, teacher support significantly moderates this relationship, increasing the effect to β = 0.497 (p = .043). Gender-based analysis shows that male students demonstrate higher levels of school engagement than females. These findings suggest that school engagement can be strengthened by enhancing students’ grit and providing supportive teacher-student interactions. The study contributes to the literature by highlighting the joint influence of personal and contextual factors on student engagement and offers practical implications for fostering academic motivation in culturally unique educational settings.